2003
DOI: 10.2116/analsci.19.1001
|View full text |Cite
|
Sign up to set email alerts
|

Reversed-phase HPLC Determination of Chlorophyll a′ and Naphthoquinones in Photosystem I of Red Algae: Existence of Two Menaquinone-4 Molecules in Photosystem I of Cyanidium caldarium

Abstract: The light reaction of oxygenic photosynthetic organisms proceeds by the cooperation of hundreds of such cofactors as chlorophyll (Chl), quinones, and carotenoids, placed within large pigment-protein complexes, photosystem (PS) I and PS II, in thylakoid membranes. Most Chl molecules function as lightharvesting pigments to funnel the excitation energy to the primary electron donor, P700 in PS I and P680 in PS II (for review, see Ref. 1). In the electron-transfer chains of PS I and PS II, minor Chl a derivatives … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…PCC 7002 were shown to contain MQ-4 instead of PhQ, the quinone present in most other cyanobacteria and higher plants. MQ-4 was recently shown to be present in the red alga C. caldarium (2) and the early diverging cyanobacterium, Gloeobacter violaceus PCC 7421 (37). These results indicate that MQ-4 may be more widely employed in PS I than was previously recognized.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PCC 7002 were shown to contain MQ-4 instead of PhQ, the quinone present in most other cyanobacteria and higher plants. MQ-4 was recently shown to be present in the red alga C. caldarium (2) and the early diverging cyanobacterium, Gloeobacter violaceus PCC 7421 (37). These results indicate that MQ-4 may be more widely employed in PS I than was previously recognized.…”
Section: Discussionmentioning
confidence: 99%
“…In most organisms, including Synechocystis sp. PCC 6803, the quinone in the A 1 site is phylloquinone (2-methyl-3-phytyl-1,4-naphthoquinone), but in Euglena gracilis and Anacystis nidulans, the quinone is 5Ј-monohydroxyphylloquinone (1), and in the red alga Cyanidium caldarium it is menaquinone-4 (MQ-4) 1 (2). Our approach to studying structural and functional relationships involving A 1 is to replace the native quinone in PS I with quinones that have different thermodynamic and structural properties but are still able to mediate electron transfer from A 0 to the Fe/S clusters.…”
mentioning
confidence: 99%
“…Specific HPLC chromatogram peaks of known proteins or the ratio of two protein peaks (e.g. flavodoxin and ferredoxin) has been used for the determination of the nutritional status of seawaters [16,18,27]. For example, Erdner and Anderson [18] …”
Section: Fluorescent-based Hplc Peaks As An Indicator Of Fe Bioavailamentioning
confidence: 99%
“…Fluorescent-based HPLC assay is a quick, easy, efficient and powerful method for the quantitative measurement of cellular macromolecules in organisms [22][23][24][25][26][27]. This method has been used for the determination of cysteine and cysteamine adducts in Escherichia coli-derived proteins [26], thiol compounds in biological samples [22], human erythrocytic glutathione [25], domoic acid (DA) in mussels (Mytilus edulis) [24], peptides in tissue and plasma samples [28] and amines and proteins [29] using different fluorescent reagents as the derivatizer.…”
Section: Introductionmentioning
confidence: 99%
“…4b) species are present and function as A 1 in their RCs. Kobayashi et al (2006a) As mentioned above, A 1 in oxygenic PS I is PhQ, however, MQ was recently reported to function as A 1 in a primitive unicellular red alga Cyanidium caldarium (Yoshida et al 2003), then in a primitive cyanobacterium G. violaceus , and a marine centric diatom Chaetoceros gracilis (Ikeda et al 2008). It has been shown that A. marina uses PhQ as A 1 (Ohashi et al 2008a).…”
Section: Introductionmentioning
confidence: 95%